Dinamika Organisasi Sosial Keagamaan di Pesisir Lamongan: Antara Inklusif dan Eksklusif - Farihah, Irzum; Susetiawan, Susetiawan; Nurhadi, Agus (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2023)
This paper aims to study and prove how the religious behavior of coastal Lamongan people in a dynamic society in search of a religious model that can provide worldly happiness and ukhrowi, using Max Weber's theoretical approach in looking at the purpose of actions taken by someone with diverse motives. Religious behavior is certainly inseparable from factors from within a person or from outside, including figures who become role models of society. Therefore, there will be a variety of religions, ranging from exclusive and inclusive. This research found that two religious organizations -Muhammadiyah and NU- which have been considered well established in The Lamongan Coast, apparently experienced changes in gaining trust related to solving the problem of immorality. Therefore, coastal communities that tend to be dynamic, try to find self-satisfaction by learning to draw closer to their Lord (Allah), by following the religious activities of new groups outside Muhammadiyah and NU. The intersubjective religious model implemented by this new group was able to open up and be accepted among the people of Lamongan Coast.